2016
DOI: 10.1530/jme-15-0251
|View full text |Cite
|
Sign up to set email alerts
|

Foxo3b but not Foxo3a activates cyp19a1a in Epinephelus coioides

Abstract: FOXO3 has been shown to be a critical transcription factor for folliculogenesis in mammals, while the information on its roles in reproduction of nonmammalian vertebrates remains scarce. In this study, two foxo3 homologs, namely foxo3a and foxo3b, were identified in a teleost, the orange-spotted grouper Epinephelus coioides. foxo3a was mainly expressed in the central nervous system, ovary, and gut whereas foxo3b was expressed ubiquitously in tissues examined. In contrast to the dominant expression of mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The bmp15, an oocyte-expressed signaling molecule, is required for maintenance of the female sexual fate in zebrafish (Dranow et al, 2016). The foxo3 is a critical transcriptional regulator of fish ovarian development by regulating the ovarian germ cells and follicular cells (Liu et al, 2016). Nr0b1, also called dax1, mainly locates in fish primary oocytes and previtellogenic oocyte cells, and its mutation in zebrafish causes female-to-male sex reversal (Chen et al, 2016).…”
Section: The Relationship Between M6a and A-to-i Editing In The Flounmentioning
confidence: 99%
“…The bmp15, an oocyte-expressed signaling molecule, is required for maintenance of the female sexual fate in zebrafish (Dranow et al, 2016). The foxo3 is a critical transcriptional regulator of fish ovarian development by regulating the ovarian germ cells and follicular cells (Liu et al, 2016). Nr0b1, also called dax1, mainly locates in fish primary oocytes and previtellogenic oocyte cells, and its mutation in zebrafish causes female-to-male sex reversal (Chen et al, 2016).…”
Section: The Relationship Between M6a and A-to-i Editing In The Flounmentioning
confidence: 99%
“…mfap4 is also shown to play an important role in the innate immune system of zebrafish (Zakrzewska et al, 2010;Walton et al, 2015) and catfish (Niu et al, 2011). Foxo3a and Foxo3b in ovarian follicular cells during vitellogenesis were significantly increased stage dependently and co-localized with CYP19a1a (Liu et al, 2016). foxo3b retained most of the functions including upregulating cyp19a1a during vitellogenesis of orange-spotted grouper (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Foxo3a and Foxo3b in ovarian follicular cells during vitellogenesis were significantly increased stage dependently and co-localized with CYP19a1a (Liu et al, 2016). foxo3b retained most of the functions including upregulating cyp19a1a during vitellogenesis of orange-spotted grouper (Liu et al, 2016). WB revealed that overexpression of miRNA-96 substantially reduced FOXO3 protein expression (Yin et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown that sf1 plays crucial roles in slider turtle sex differentiation and determination [ 43 ] and is an essential regulator of gonad development in Nile tilapia [ 44 ]. Foxo3 has been shown to be involved in ovarian development in the Gobiocypris rarus [ 45 ], and it upregulates cyp19a1a during vitellogenesis in the orange-spotted grouper [ 46 ]. Gata4 is not only required for gonad differentiation in tilapia but also important to gonad development and maturation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%